Orbital Metastasis Is Associated With Decreased Survival in Stage M Neuroblastoma. Issue 4 (24th November 2015) - Harreld, Julie H.; Bratton, Emily M.; Federico, Sara M.; Li, Xingyu; Grover, William; Li, Yimei; Kerr, Natalie C.; Wilson, Matthew W.; Hoehn, Mary E.
Abstract : Background: Approximately 30% of patients with metastatic (stage M) neuroblastoma present with periorbital ecchymosis from orbital osseous disease. Though locoregional disease is staged by imaging, the prognostic significance of metastatic site in stage M disease is unknown. We hypothesize that, compared to nonorbital metastasis, orbital metastasis is associated with decreased survival in patients with stage M neuroblastoma, and that periorbital ecchymosis reflects location and extent of orbital disease. Procedure: Medical records and imaging from 222 patients with stage M neuroblastoma seen at St. Jude Children's Research Hospital between January 1995 and May 2009 were reviewed. Thirty‐seven patients were <18 months of age at diagnosis and 185 were ≥18 months of age. Overall survival (OS) and 5‐year survival (5YS) were compared for patients with and without orbital, calvarial and nonorbital osseous metastasis, and with and without periorbital ecchymosis (log‐rank test). Associations of periorbital ecchymosis with orbital metastasis location/extent were explored (Fisher's exact test, t ‐test). Results: In patients ≥18 months of age, only orbital metastasis was associated with decreased 5YS ( P = 0.0323) and OS ( P = 0.0288). In patients <18 months of age, neither orbital, calvarial, or nonorbital bone metastasis was associated with OS or 5YS. Periorbital ecchymosis was associated with higher number of involved orbital bones ( P = 0.0135), but not location or survival. Conclusions: In patients ≥ 18 months of age with stage M neuroblastoma, orbital metastatic disease is associated with decreased 5YS and OS. In future clinical trials, orbital disease may be useful as an imaging‐based risk factor for substratification of stage M neuroblastoma.